Cyber Crime “Phishing” In Islamic Law - -, Putri Avini Azzahra (UMBanjarmasin, 2024)
In the are of increasing globalizing and also with increasing technological development, phising is happening all around us. In cyberspace, there are a lot of fraunds that occur both knowningly and unknowingly. And what islam think about this phishing.This journal reviews phishing frpm an islamic perspective, how Islam deals with it and it is hoped that by writing this journal, it will be able to find out whT Islam viewa about cyber crime phishing and this writing aims fo find out what cyber crime phishing is, as well as islamic opinions about cyber crime, with this writing, it hoped that readers willl understand and be able to avoid cyber crime phishing. This writing usesliterature tudy method where empirical data is sought from journals